Potencial reproductivo, tasa de crecimiento y ambiente lumínico en Lepanthes rupestris Stimson - Fernández, Denny S. (Universidad de Costa Rica, 2016)
Reproductive success in orchids can be pollinator or resource limited (Ackerman & Montalvo 1990). However, orchids are generally pollinator limited (Neiland & Wilcock 1998), while some species have shown to be resource limited as a function of lifetime reproductive success (Whigham & O’Neill 1991, Meléndez-Ackerman et al. 2000).